The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5888/pcd14.170003
|View full text |Cite
|
Sign up to set email alerts
|

Teaming Up for Asthma Control: EPR-3 Compliant School Program in Missouri Is Effective and Cost-Efficient

Abstract: IntroductionTeaming Up for Asthma Control (TUAC) is a work force development intervention to improve asthma control among children by increasing the competency of school nurses and delivering guideline-based education. We hypothesized that the knowledge and skills of participating school nurses would improve and that this change would positively affect students’ asthma health and reduce health care utilization cost.MethodsAsthma education for school nurses was provided online in a pretest/posttest format or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…School nurse management of chronic disease was used to explore health outcome measures. Five studies addressed health outcome measures in children diagnosed with asthma: overall asthma and medication knowledge (Francisco et al, 2017; Mickel et al, 2017), health-care cost savings, number of days with/without asthma symptoms, quality of life, activity limitations, readiness to change stages, student perceptions about asthma, and asthma management barriers (Francisco et al, 2017; Halterman et al, 2011; Krenitsky-Korn, 2011; Quaranta & Spencer, 2016). Spina, McIntyre, and Pulcini (2012) and Szychlinski et al (2015) measured the number of students with available epinephrine pens, number of times epinephrine was administered, types of personnel available to respond to emergencies, reasons epinephrine was not administered, and types of school communities that do not have epinephrine available.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…School nurse management of chronic disease was used to explore health outcome measures. Five studies addressed health outcome measures in children diagnosed with asthma: overall asthma and medication knowledge (Francisco et al, 2017; Mickel et al, 2017), health-care cost savings, number of days with/without asthma symptoms, quality of life, activity limitations, readiness to change stages, student perceptions about asthma, and asthma management barriers (Francisco et al, 2017; Halterman et al, 2011; Krenitsky-Korn, 2011; Quaranta & Spencer, 2016). Spina, McIntyre, and Pulcini (2012) and Szychlinski et al (2015) measured the number of students with available epinephrine pens, number of times epinephrine was administered, types of personnel available to respond to emergencies, reasons epinephrine was not administered, and types of school communities that do not have epinephrine available.…”
Section: Resultsmentioning
confidence: 99%
“…School nurses attended continuing education on the overall health of students diagnosed with asthma and training to conduct assessments, use equipment (e.g., peak flow meters), and implement action plans (Carpenter et al, 2013;Francisco, Rood, Nevel, Foreman, & Homan, 2017;Putman-Casdorph & Pinto, 2011;Staudt, Alamgir, Long, Inscore, & Wood, 2015). Other studies included education for school nurses about food allergies (Chokshi, Patel, & Davis, 2015), adolescent relationship abuse and how to integrate discussions of healthy/unhealthy relationships in each student encounter (Raible et al, 2017), school preparedness for biological events (Rebmann, Elliott, Artman, VanNatta, & Wakefield, 2016), how to support students as they return to the classroom (i.e., return to learn) after concussions (Wing, Amanullah, Jacobs, Clark, & Merritt, 2015), recognizing children at risk for maltreatment (Jordan, MacKay, & Woods, 2017), and improving communication with families on weight-related health issues through a web-based tutorial (Steele, Wu, Cushing, & Jensen, 2013).…”
Section: School Nurse Interventions and Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Several research studies have cited positive outcomes through the use of community-based asthma education programs. 12,[14][15][16][17] As a result of the education provided within these studies, several outcomes demonstrated improvements, such as enhanced knowledge; better controlled asthma; fewer emergency department visits, hospitalizations, and school absences; increased health promotion behaviors and quality of life; and improved communication with and access to health care providers. 12,[14][15][16][17] The connection with the community illustrated in these studies can also be applied to the school setting.…”
Section: Education and Prevention Program Developed The Expertmentioning
confidence: 99%